Leishmania-HIV co-infection: clinical presentation and outcomes in an urban area in Brazil. - Gláucia F Cota; Marcos R de Sousa; Andrea Laender Pessoa de Mendonça; Allan Patrocinio; Luiza Siqueira Assunção; Sidnei Rodrigues de Faria; Ana Rabello (Public Library of Science (PLoS), 2014)
BACKGROUND: Visceral leishmaniasis (VL) is an emerging condition affecting HIV-infected patients living in Latin America, particularly in Brazil. Leishmania-HIV coinfection represents a challenging diagnosis because the clinical picture of VL is similar to that of other disseminated opportunistic diseases. Additionally, coinfection is related to treatment failure, relapse and high mortality. OBJECTIVE: To assess the clinical-laboratory profile and outcomes of VL-HIV-coinfected patients using a group of non HIV-infected patients diagnosed with VL during the same period as a comparator. METHODS: The study was conducted at a reference center for infectious diseases in Brazil. All patients with suspected VL were evaluated in an ongoing cohort study. Confirmed cases were divided into two groups: with and without HIV coinfection. Patients were treated according to the current guidelines of the Ministry of Health of Brazil, which considers antimony as the first-choice therapy for non HIV-infected patients and recommends amphotericin B for HIV-infected patients. After treatment, all patients with CD4 counts below 350 cells/mm3 received secondary prophylaxis with amphotericin B. RESULTS: Between 2011 and 2013, 168 patients with suspected VL were evaluated, of whom 90 were confirmed to have VL. In total, 51% were HIV coinfected patients (46 patients). HIV-infected patients had a lower rate of fever and splenomegaly compared with immunocompetent patients. The VL relapse rate in 6 months was 37% among HIV-infected patients, despite receiving secondary prophylaxis. The overall case-fatality rate was 6.6% (4 deaths in the HIV-infected group versus 2 deaths in the non HIV-infected group). The main risk factors for a poor outcome at 6 months after the end of treatment were HIV infection, bleeding and a previous VL episode. CONCLUSION: Although VL mortality rates among HIV-infected individuals are close to those observed among immunocompetent patients treated with amphotericin B, HIV coinfection is related to a low clinical response and high relapse rates within 6 months.